(untitled) (Scientific journal of the Fergana State University, 2023)
Find out the literary and aesthetic views of the writer, study a number of literary works and journalistic genres that express the personal position of the writer to the world and man, determine the manifestation of the literary and aesthetic views of the writer. in two types of work. To clarify the research topic, analytical, comparative-typological, comparative-historical, psychological, structural, hermeneutic methods of analysis were used. Questions of literary and aesthetic views of the writer and the psychology of the creator, the aesthetic ideal of the writer were determined on the basis of advanced approaches of modern literary criticism. The manifestation of the literary and aesthetic views of Erkin Azam is revealed through the analysis of his articles, poems, memoirs, travel stories included in the collection "Morning Dreams". A great influence on the formation of the literary and aesthetic views of Erkin Azam was exerted by such factors as the family environment, the literary environment, artistic and aesthetic experience and traditions, and the socio-political environment. The creativity of teachers and peers, such as Abdullah Kahkhor, Askad Mukhtar, also had a great positive impact. Erkin Azam created literary journalism in such genres as a literary article, interview, memoir, guidebook, fikra, literary portrait, rich in presentation, cuts, analysis of life and literary examples, interpretation of universal ideas. The creativity of teachers and peers, such as Abdullah Kahkhor, Askad Mukhtar, also had a great positive impact. Erkin Azam created literary journalism in such genres as a literary article, interview, memoir, guidebook, fikra, literary portrait, rich in presentation, cuts, analysis of life and literary examples, interpretation of universal ideas.